Composition of M,N-adhesive Categories with Application to Attribution of Graphs - Peuser, Christoph; Habel, Annegret (Electronic Communications of the EASST, 2016)
This paper continues the work on M,N-adhesive categories and shows some important composition properties for these categories. We present a new concept of attributed graphs and show that the corresponding category is M,N-adhesive. As a consequence, we inherit all nice properties for M,N-adhesive systems such as the Local Church-Rosser Theorem, the Parallelism Theorem, and the Concurrency Theorem for this type of attributed graphs.